2022
DOI: 10.1038/s41588-021-01010-x
|View full text |Cite
|
Sign up to set email alerts
|

GestaltMatcher facilitates rare disease matching using facial phenotype descriptors

Abstract: The majority of monogenic disorders cause craniofacial abnormalities with characteristic facial morphology. These disorders can be diagnosed more e ciently with the support of computer-aided nextgeneration phenotyping tools, such as DeepGestalt. These tools have learned to associate facial phenotypes with the underlying syndrome through training on thousands of patient photographs. However, this "supervised" approach means that diagnoses are only possible if they were part of the training set. To improve recog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(134 citation statements)
references
References 42 publications
(25 reference statements)
1
94
0
2
Order By: Relevance
“…We applied GestaltMatcher 22 to compare facial phenotypes among individuals with variants in CSNK2B . The detailed method of GestaltMatcher is provided in the extended supplemental material and methods .…”
Section: Methodsmentioning
confidence: 99%
“…We applied GestaltMatcher 22 to compare facial phenotypes among individuals with variants in CSNK2B . The detailed method of GestaltMatcher is provided in the extended supplemental material and methods .…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated Face2Gene is as good as or superior to clinical assessments performed by trained healthcare providers in identifying genetic disorders ( Basel-Vanagaite et al, 2016 ; Gripp et al, 2016 ; Liehr et al, 2018 ; Pantel et al, 2018 ; Vorravanpreecha et al, 2018 ). In a very recent study, GestaltMatcher, an encoder based on deep convolutional neural networks, matched patients with other patients with the same molecular diagnosis, even if the disorder was not included in the training set ( Hsieh et al, 2022 ). This program could accelerate the clinical diagnosis of patients with extremely rare diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning technology has been able to take advantage of this observation and several tools have been developed to match facial phenotypes with known syndromes (Gurovich et al, 2019; Huang et al, 2008; Pantel et al, 2020; Taigman et al, 2014). Most recently machine vision tools have shown potential for applications in diagnosing and characterizing ultra-rare syndromes with the added benefit of being minimally invasive (van der Donk et al, 2019; Hsieh et al, 2022). However the majority of craniofacial abnormalities are much more common than these syndromes and occur in the absence of other abnormalities (Leslie and Marazita, 2013; Morris, 2016).…”
Section: Introductionmentioning
confidence: 99%